Follow-Up of Newborns with Neural Tube Defects: A Single Center Experience - Umit Ayse Tandircioglu; Cansu Kethuda Ensert Cihan; Hasan Tolga Celik; Burcak Bilginer; Sule Yigit (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Neural tube defects, defined as the developmental malformations of the central nervous system, are seen in our country at a rate of three per thousand on average. Our study aims to retrospectively evaluate patients with neural tube defects hospitalized in our intensive care unit for the last decade.